2006
DOI: 10.1111/j.1399-0012.2006.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Are personnel in transplant hospitals in favor of cadaveric organ donation? Multivariate attitudinal study in a hospital with a solid organ transplant program

Abstract: Attitude toward cadaveric organ donation among personnel in a transplant hospital is similar to that described in the general public and is determined by many factors. The following factors are most noteworthy: (i) job category; (ii) knowledge of the concept of brain death; (iii) consideration of the matter of donation in the family; and (iv) fear of manipulation of the cadaver. In view of this attitude, which is similar to that of the general public, it is necessary to carry out promotion activities if we wan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 23 publications
7
40
2
3
Order By: Relevance
“…[24][25][26] Most studies that have examined this matter of brain death knowledge have shown a close association between the knowledge and acceptance of the concept of brain death and attitude toward organ donation and transplantation. 7,9,17,18,27 However, in this study, this association was not found. It is possible that the lack of awareness about this matter, in which only 25% of those surveyed accepted that it means a person's death, can account for these data.…”
Section: Antonio Ríos Et Al/experimental and Clinical Transplantationcontrasting
confidence: 53%
See 1 more Smart Citation
“…[24][25][26] Most studies that have examined this matter of brain death knowledge have shown a close association between the knowledge and acceptance of the concept of brain death and attitude toward organ donation and transplantation. 7,9,17,18,27 However, in this study, this association was not found. It is possible that the lack of awareness about this matter, in which only 25% of those surveyed accepted that it means a person's death, can account for these data.…”
Section: Antonio Ríos Et Al/experimental and Clinical Transplantationcontrasting
confidence: 53%
“…There is a clear relation between this fear and the discovery of brain death. [14][15][16][17][18] Studies of the Spanish population have shown that the lack of understanding of the brain death concept and the fear of apparent death in the donation process was at one point as high as 70% to 80%. 19 Although these data have improved, presently, nearly 50% of the Spanish population do not know this concept, and its misconception continues to be an independent factor affecting attitude toward deceased organ donation.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the situation in attitude toward deceased organ donation 20,21 no differences have been found in terms of job category or other variables of this nature, but they have emotional and other factors related directly or indirectly with donation and transplantation. 22,23 As shown in Table 2, a favorable attitude toward deceased organ donation is a factor which encourages a positive attitude toward living donation.…”
Section: Discussionmentioning
confidence: 87%
“…Evaluaron la actitud y el conocimiento general hacia la donación y el trasplante de órganos. Las encuestas constaban de 34 preguntas de opción múl-tiple y fueron obtenidas de un cuestionario validado de actitud hacia la donación y el trasplante de órga-nos (PCID-DTO RIOS: Cuestionario de «Proyecto Colaborativo Internacional Donante» sobre donación y trasplante de órganos desarrollado por Ríos et al) (véase anexo) [5][6][7] . De cada cuestionario se evaluaron la actitud de los estudiantes hacia la donación de órganos, los aspectos sociodemográficos, de conducta prosocial, de información y de conocimiento sobre donación de órganos, de interacciones familiares y sociales, socioculturales y de actitud sobre el cuerpo.…”
Section: Métodosunclassified